Preparation process of durable pressing silk-cotton yarn-dyed fabric

By soaking silk fibers in anti-wrinkle reagents to form an anti-wrinkle coating, the problem that silk cotton fabrics are prone to wrinkles after folding or washing with water is solved, and the good wrinkle resistance, water washing and UV resistance of silk cotton woven fabrics is achieved.

CN119433990APending Publication Date: 2025-02-14NANTONG BOYING TEKUO WEAVING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411558459.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Silk cotton fabrics are prone to folding or wrinkles after being folded or washed, affecting the beauty and tidyness of the fabric.

Method used

A durable ironing cotton colored weaving fabric preparation process is adopted. By soaking silk fibers in anti-wrinkle reagents, an anti-wrinkle coating is formed to enhance the anti-wrinkle properties of silk fibers. Anti-wrinkle agents include aqueous polyurethane emulsions, polyetheramine composite anti-wrinkle agents, anti-ultraviolet agents, dispersants and leveling agents.

Benefits of technology

It significantly improves the wrinkle resistance and water washing resistance of silk cotton woven fabrics, and at the same time improves the UV resistance, making the fabric more durable and stable after folding and water washing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117206610000071
    Figure BDA0005117206610000071
  • Figure BDA0005117206610000081
    Figure BDA0005117206610000081
Patent Text Reader

Abstract

The invention relates to a durable pressing silk cotton yarn-dyed fabric preparation process which comprises the following steps: soaking silk fibers into an anti-wrinkle reagent, standing to enable the anti-wrinkle reagent to be in full contact with the silk fibers, then taking out and drying the silk fibers to obtain treated silk fibers, spinning the treated silk to obtain a silk fabric, and drying the silk fabric to obtain the durable pressing silk cotton yarn-dyed fabric. The method comprises the following steps: dyeing silk cloth, and drying to obtain silk floss yarn-dyed fabric; the anti-wrinkle reagent is prepared from 180 to 200 parts of waterborne polyurethane emulsion, 21 to 31 parts of polyether amine composite anti-wrinkle agent, 14 to 20 parts of anti-ultraviolet agent, 3 to 5 parts of dispersing agent and 2 to 4 parts of flatting agent, and the polyether amine composite anti-wrinkle agent is prepared from a polyether amine compound A, a polyether amine compound B and an emulsifying agent. The method has the effect of improving the anti-wrinkle performance of the silk floss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fabrics, and in particular to a process for preparing durable press-ironing silk-cotton yarn-dyed fabrics. Background Art

[0002] Silk cotton fabric is a kind of fabric made from mulberry silk and is a green and environmentally friendly product.

[0003] Silk cotton fabric is a natural fiber cotton fabric. After being folded or washed, it is easy to produce creases or wrinkles, which affects the overall beauty and neatness of the fabric, so it is effectively improved. Summary of the invention

[0004] In order to improve the wrinkle resistance of silk cotton fabrics, the present application provides a process for preparing durable pressed silk cotton yarn-dyed fabrics.

[0005] The present application provides a durable pressing silk-cotton yarn-dyed fabric preparation process using the following technical solutions: A process for preparing durable pressing silk-cotton yarn-dyed fabric comprises the following steps: The silk fibers are soaked in an anti-wrinkle agent, and allowed to stand to allow the anti-wrinkle agent to fully contact the silk fibers, and then the silk fibers are taken out and dried to obtain treated silk fibers, and the treated silk fibers are spun to obtain silk fabrics, and the silk fabrics are dyed and dried to obtain silk cotton yarn-dyed fabrics; The anti-wrinkle agent comprises 180-200 parts of waterborne polyurethane emulsion, 21-31 parts of polyetheramine composite anti-wrinkle agent, 14-20 parts of anti-ultraviolet agent, 3-5 parts of dispersant and 2-4 parts of leveling agent. The polyetheramine composite anti-wrinkle agent comprises polyetheramine compound A, polyetheramine compound B and emulsifier.

[0006] By adopting the above technical scheme, after the silk fiber is soaked in the anti-wrinkle agent, a layer of anti-wrinkle coating is attached to the original surface of the silk, and the silk fabric obtained by weaving the silk with the anti-wrinkle coating has good anti-wrinkle performance, effectively reducing the phenomenon of wrinkles when the fabric is folded, and the anti-wrinkle coating is added with polyetheramine complex A, polyetheramine complex B and emulsifier, and the amino group and epoxy group are ring-opened to prepare a polyetheramine composite anti-wrinkle agent, which can form a film on the surface of the silk fiber. It is tightly adsorbed on the surface of the silk fiber to increase the overall contact angle of the silk fiber, and certain wrinkles are formed on the surface of the silk fiber, so that the elasticity of the silk fiber is improved, the anti-wrinkle performance of the silk fiber is improved, and the anti-wrinkle performance of the prepared silk cotton yarn-dyed fabric is improved.

[0007] Preferably, the polyetheramine composite anti-wrinkle agent is prepared by the following method: The tetraethyl orthosilicate, polyetheramine ED-600 and acetic acid solution are mixed and dissolved in isopropanol to obtain polyetheramine complex A; polyetheramine T-403 and tetraethyl orthosilicate are mixed to obtain polyetheramine complex B; polyetheramine complex A and polyetheramine complex B are mixed and reacted to obtain an organosilicon composite system; an emulsifier is added to the organosilicon composite system and stirred to obtain a polyetheramine composite anti-wrinkle agent.

[0008] By adopting the above technical scheme, after the prepared polyetheramine composite anti-wrinkle agent is attached to the surface of silk fibers, the cyclic chain siloxane of the silicone preform restricts the movement of the polysiloxane chain segments on the fiber surface, so that the prepared silk cotton color-dyed fabric has good water-washing resistance and anti-wrinkle performance.

[0009] Preferably, the mass ratio of the polyetheramine complex A, the polyetheramine complex B and the emulsifier is 0.58:1:(0.17-0.21).

[0010] By adopting the above technical solution, preferably the mass ratio of the polyetheramine complex A, the polyetheramine complex B and the emulsifier is within the above range, which can effectively improve the stability of the polyetheramine composite anti-wrinkle agent.

[0011] Preferably, the emulsifier includes dodecyldimethylbenzyl ammonium chloride, hexadecyltrimethylammonium chloride, isomeric alcohol ether 1306 and isomeric alcohol ether 1308.

[0012] By adopting the above technical solution, the emulsifier prepared by using a composite of multiple components can further improve the overall balance of the polyetheramine composite anti-wrinkle agent, thereby making the polyetheramine composite anti-wrinkle agent more stable on the surface of silk fibers.

[0013] Preferably, the anti-ultraviolet agent comprises a nitrogen-boron complex, 1,4-butanediol and a finishing agent.

[0014] Preferably, the anti-ultraviolet agent is prepared by the following method: Ethyl acetate, hexamethylene diisocyanate, a finishing agent, water and gum arabic are mixed, and stirred until the system is completely dissolved to obtain a mixture. 1,4-butanediol is added to the mixture, and the mixture is heated and stirred to react to obtain a suspension. A nitrogen-boron complex is added to the suspension, and an anti-ultraviolet agent is obtained by ultrasonication.

[0015] By adopting the above technical scheme, a microcapsule finishing agent is obtained by compounding a nitrogen-boron complex and a suspension, so that the anti-ultraviolet agent is fixed to the surface of the silk fiber, so that the silk fiber has good anti-ultraviolet performance. At the same time, the prepared anti-ultraviolet agent is evenly distributed on the surface of the silk fiber, thereby improving the overall stability of the prepared silk cotton color-woven fabric.

[0016] Preferably, the finishing agent is isophorone diisocyanate.

[0017] By adopting the above technical scheme, isophorone diisocyanate is used as a finishing agent, which has strong activity and can improve the overall binding performance of the prepared anti-ultraviolet agent and the silk fiber, so that the anti-wrinkle agent and the silk fiber can be stably combined, thereby improving the overall stability of the silk fiber, so that the prepared silk cotton color-woven fabric has good anti-wrinkle performance, water washability and anti-ultraviolet performance.

[0018] Preferably, the mass ratio of the nitrogen-boron complex, 1,4-butanediol and isophorone diisocyanate is (3.1-3.5):1:5.04.

[0019] By adopting the above technical solution, preferably the mass ratio of the nitrogen-boron complex, 1,4-butanediol and isophorone diisocyanate is within the above range, which can further improve the stability of the prepared anti-ultraviolet agent.

[0020] Preferably, the stirring temperature of the temperature-raising reaction is 45-55°C.

[0021] Preferably, the nitrogen-boron composite is prepared by the following method: Mix citric acid, ethylenediamine, boric acid and water, stir and react to obtain a nitrogen-boron complex.

[0022] By adopting the above technical scheme, citric acid is used as the carbon source, and after adding boric acid and ethylenediamine, the nitrogen-boron complex can be obtained, which can effectively improve the overall anti-ultraviolet performance of silk fibers. At the same time, the nitrogen-boron complex has abundant active groups such as hydroxyl and amino groups, and its compatibility in the system is improved, so that the anti-ultraviolet agent is more stable, thereby improving the prepared silk cotton-dyed fabric with good stability and ultraviolet resistance.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. After the silk fiber is soaked in the anti-wrinkle agent, a layer of anti-wrinkle coating is formed on the surface of the silk fiber, and the silk cotton yarn-dyed fabric woven from the treated silk fiber has good anti-wrinkle performance; after the polyether composite anti-wrinkle agent in the anti-wrinkle agent adheres to the surface of the silk fiber, it can form a film on the surface of the silk fiber and be tightly adsorbed on the surface of the silk fiber, thereby increasing the overall contact angle of the silk fiber and forming wrinkles on the surface of the silk fiber, thereby improving the elasticity of the silk fiber, and further improving the anti-wrinkle property of the prepared silk fabric; 2. When preparing the polyether composite anti-wrinkle agent, the emulsifier obtained by compounding multiple agents can promote the overall water-oil balance of the system, so that the prepared polyether anti-wrinkle agent has good stability, and can improve the average particle size of the emulsion, so that the polyether composite anti-wrinkle agent can be more stably combined on the surface of silk fibers; 3. An anti-ultraviolet agent is prepared by compounding a nitrogen-boron complex with a suspension, and a microcapsule emulsion is obtained. The nitrogen-boron complex prepared by using citric acid as a nitrogen source and adding boric acid and ethylenediamine has good anti-ultraviolet properties. The wall material of the anti-ultraviolet composite agent has good stability after cross-linking with the fabric surface, which also improves the washability of the silk fabric. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments: Raw material description: All raw materials in the examples can be obtained commercially; in the anti-wrinkle agent, the dispersant is diethylenetriamine penta (methylenephosphonic acid) (CAS No.: 15827-60-8), and the leveling agent is BYK-392.

[0025] Example 1 Preparation of UV-resistant reagent: 1.05 g of citric acid (CAS No.: 77-92-9), 1.25 g of ethylenediamine, 3 g of boric acid and 150 g of deionized water were mixed, the temperature was raised to 160° C. and stirred at a speed of 100 r / min for 6 hours to obtain a nitrogen-boron complex.

[0026] 2.75 g of ethyl acetate, 4.05 g of hexamethylene diisocyanate (CAS No.: 822-06-0), 11.08 g of a finishing agent, 100 g of deionized water, and 4 g of gum arabic were mixed, the temperature was raised to 35° C. and stirred until the system was completely dissolved to obtain a mixture, 2.2 g of 1,4-butanediol (CAS No.: 110-63-4) was added to the mixture, the temperature was raised to 45° C., and the reaction was stirred at a speed of 600 r / min for 1.5 hours to obtain a suspension; 6.82 g of a nitrogen-boron complex was added to the suspension, and ultrasonic treatment was performed for 5 minutes to obtain an anti-ultraviolet agent.

[0027] The finishing agent is isophorone diisocyanate (CAS No.: 4098-71-9).

[0028] Preparation of polyetheramine composite anti-wrinkle agent: 24.39 g of tetraethyl orthosilicate, 5.61 g of polyetheramine ED-600 (CAS No.: 9046-10-0) and 20 g of 10% acetic acid solution were mixed, and dissolved in 100 g of isopropanol with a mass fraction of 83% at 40° C. to obtain polyetheramine complex A; 28.57 g of polyetheramine T-403 (CAS No.: 39423-51-3) and 11.43 g of tetraethyl orthosilicate were mixed to obtain polyetheramine complex B; 16.57 g of polyetheramine complex A and 28.57 g of polyetheramine complex B were mixed, and reacted at 40° C. for 8 hours to obtain an organosilicon composite system; 4.45 g of dodecyldimethylbenzyl ammonium chloride (CAS No.: 139-07-1), 2.27 g of hexadecyltrimethylammonium chloride (CAS No.: 112-02-7), 1.78 g of isomeric alcohol ether 1306 (CAS No.: 69011-36-5) and 1.5 g of isomeric alcohol ether 1308 (CAS No.: 9043-30-5) were mixed, and the mixture was mixed at a speed of 150 r / min for 5 min to obtain an emulsifier. 4.86 g of the emulsifier was added to the silicone composite system, and the mixture was stirred at a speed of 1000 r / min for 20 min in a water bath at 40°C to obtain a polyetheramine composite anti-wrinkle agent.

[0029] Preparation of anti-wrinkle reagent: 180 g of aqueous polyurethane emulsion, 21 g of polyetheramine composite anti-wrinkle agent, 14 g of anti-ultraviolet agent, 3 g of dispersant and 2 g of leveling agent were mixed, and stirred at a speed of 200 r / min for 20 min to obtain an anti-wrinkle agent.

[0030] Preparation of silk cotton yarn-dyed fabric: The silk fibers are immersed in an anti-wrinkle agent and allowed to stand for 2 hours to allow the anti-wrinkle agent to fully contact the silk fibers. The silk fibers are then taken out and dried in an environment of 45°C for 12 hours to obtain treated silk fibers. The treated silk is spun to obtain silk cloth. The silk cloth is dyed and dried in an oven at 45°C for 6 hours to obtain silk-dyed fabric.

[0031] Example 2 Preparation of UV-resistant reagent: 1.05 g of citric acid, 1.25 g of ethylenediamine, 3 g of boric acid and 150 g of deionized water were mixed, the temperature was raised to 160° C. and stirred at a speed of 100 r / min for 6 h to obtain a nitrogen-boron complex.

[0032] 2.75 g of ethyl acetate, 4.05 g of hexamethylene diisocyanate, 10.62 g of isophorone diisocyanate, 100 g of deionized water, and 4 g of gum arabic were mixed, the temperature was raised to 35° C. and stirred until the system was completely dissolved to obtain a mixture, 2.1 g of 1,4-butanediol was added to the mixture, the temperature was raised to 55° C., and the reaction was stirred at a speed of 600 r / min for 1.5 hours to obtain a suspension; 7.35 g of a nitrogen-boron complex was added to the suspension, and ultrasonic treatment was performed for 5 minutes to obtain an anti-ultraviolet agent.

[0033] Preparation of polyetheramine composite anti-wrinkle agent: 24.39 g of tetraethyl orthosilicate, 5.61 g of polyetheramine ED-600 and 20 g of 10% acetic acid solution were mixed and dissolved in 100 g of isopropanol with a mass fraction of 83% at 40°C to obtain polyetheramine complex A; 28.57 g of polyetheramine T-403 and 11.43 g of tetraethyl orthosilicate were mixed to obtain polyetheramine complex B; 16.2 g of polyetheramine complex A and 29.73 g of polyetheramine complex B were mixed and reacted at 40°C. The mixture was stirred for 8 hours to obtain a silicone composite system; 4.45 g of dodecyldimethylbenzylammonium chloride, 2.27 g of hexadecyltrimethylammonium chloride, 1.78 g of isomeric alcohol ether 1306 and 1.5 g of isomeric alcohol ether 1308 were mixed, and the mixture was mixed at a speed of 150 r / min for 5 minutes to obtain an emulsifier; 5.87 g of the emulsifier was added to the silicone composite system, and the mixture was stirred at a speed of 1000 r / min for 20 minutes in a water bath at 40°C to obtain a polyetheramine composite anti-wrinkle agent.

[0034] Preparation of anti-wrinkle reagent: 190 g of aqueous polyurethane emulsion, 26 g of polyetheramine composite anti-wrinkle agent, 17 g of anti-ultraviolet agent, 4 g of dispersant and 3 g of leveling agent were mixed, and stirred at a speed of 200 r / min for 20 min to obtain an anti-wrinkle agent.

[0035] Preparation of silk cotton yarn-dyed fabric: The silk fibers are immersed in an anti-wrinkle agent and allowed to stand for 2 hours to allow the anti-wrinkle agent to fully contact the silk fibers. The silk fibers are then taken out and dried in an environment of 45°C for 12 hours to obtain treated silk fibers. The treated silk is spun to obtain silk cloth. The silk cloth is dyed and dried in an oven at 45°C for 6 hours to obtain silk-dyed fabric.

[0036] Example 3 Preparation of UV-resistant reagent: 1.05 g of citric acid, 1.25 g of ethylenediamine, 3 g of boric acid and 150 g of deionized water were mixed, the temperature was raised to 160° C. and stirred at a speed of 100 r / min for 6 h to obtain a nitrogen-boron complex.

[0037] 2.75 g of ethyl acetate, 4.05 g of hexamethylene diisocyanate, 10.84 g of isophorone diisocyanate, 100 g of deionized water, and 4 g of gum arabic were mixed, the temperature was raised to 35° C. and stirred until the system was completely dissolved to obtain a mixture, 2.16 g of 1,4-butanediol was added to the mixture, the temperature was raised to 50° C., and the reaction was stirred at a speed of 600 r / min for 1.5 hours to obtain a suspension; 7 g of a nitrogen-boron complex was added to the suspension, and ultrasonic treatment was performed for 5 minutes to obtain an anti-ultraviolet agent.

[0038] Preparation of polyetheramine composite anti-wrinkle agent: 24.39 g of tetraethyl orthosilicate, 5.61 g of polyetheramine ED-600 and 20 g of 10% acetic acid solution were mixed and dissolved in 100 g of isopropanol with a mass fraction of 83% at 40°C to obtain polyetheramine complex A; 28.57 g of polyetheramine T-403 and 11.43 g of tetraethyl orthosilicate were mixed to obtain polyetheramine complex B; 16.38 g of polyetheramine complex A and 28.25 g of polyetheramine complex B were mixed and dissolved in 100 g of isopropanol with a mass fraction of 83% at 40°C to obtain polyetheramine complex B. The mixture was reacted for 8 h to obtain an organosilicon composite system; 4.45 g of dodecyldimethylbenzylammonium chloride, 2.27 g of hexadecyltrimethylammonium chloride, 1.78 g of isomeric alcohol ether 1306 and 1.5 g of isomeric alcohol ether 1308 were mixed, and the mixture was mixed at a speed of 150 r / min for 5 min to obtain an emulsifier; 5.37 g of the emulsifier was added to the organosilicon composite system, and the mixture was stirred at a speed of 1000 r / min for 20 min in a water bath at 40°C to obtain a polyetheramine composite anti-wrinkle agent.

[0039] Preparation of anti-wrinkle reagent: 190 g of aqueous polyurethane emulsion, 26 g of polyetheramine composite anti-wrinkle agent, 17 g of anti-ultraviolet agent, 4 g of dispersant and 3 g of leveling agent were mixed, and stirred at a speed of 200 r / min for 20 min to obtain an anti-wrinkle agent.

[0040] Preparation of silk cotton yarn-dyed fabric: The silk fibers are immersed in an anti-wrinkle agent and allowed to stand for 2 hours to allow the anti-wrinkle agent to fully contact the silk fibers. The silk fibers are then taken out and dried in an environment of 45°C for 12 hours to obtain treated silk fibers. The treated silk is spun to obtain silk cloth. The silk cloth is dyed and dried in an oven at 45°C for 6 hours to obtain silk-dyed fabric.

[0041] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing the polyetheramine composite anti-wrinkle agent, 16.96g of polyetheramine complex A, 29.24g of polyetheramine complex B and 3.8g of emulsifier are used.

[0042] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing the polyetheramine composite anti-wrinkle agent, 15.85 g of polyetheramine compound A and 27.32 g of polyetheramine compound B are used. The emulsifier is 6.83 g.

[0043] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the polyetheramine composite anti-wrinkle agent, the emulsifier is only hexadecyltrimethylammonium chloride.

[0044] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the anti-ultraviolet agent, 5.86 g of boron nitride complex, 2.34 g of 1,4-butanediol, and 11.8 g of isophorone diisocyanate are used.

[0045] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, when preparing the anti-ultraviolet agent, 7.97 g of boron nitride complex, 1.99 g of 1,4-butanediol, and 10.04 g of isophorone diisocyanate are used.

[0046] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the anti-ultraviolet agent, the finishing agent is replaced by toluene diisocyanate (CAS No.: 26471-62-5).

[0047] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, when preparing the anti-ultraviolet agent, when preparing the mixture, the temperature of the heating reaction after adding 1,4-butanediol is 30°C.

[0048] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, when preparing the anti-ultraviolet agent, when preparing the mixture, the temperature of the heating reaction after adding 1,4-butanediol is 70°C.

[0049] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, the nitrogen-boron complex is replaced by boron nitride.

[0050] Embodiment 13 Example 13 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, when preparing the anti-ultraviolet agent, only the nitrogen-boron complex and the finishing agent are ultrasonically prepared.

[0051] Comparative Example 1 Comparative Example 1 is based on Example 3. The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the polyetheramine composite anti-wrinkle agent is replaced by an anti-wrinkle agent prepared by only compounding tetraethyl orthosilicate and an emulsifier.

[0052] Comparative Example 2 Comparative Example 2 is based on Example 3. The difference between Comparative Example 2 and Example 3 is that the anti-ultraviolet agent prepared in Comparative Example 2 is only a silicone composite system.

[0053] Performance testing The following performance tests were performed on the samples of Examples 1-13 and Comparative Examples 1-2: (1) Anti-wrinkle performance Using GB / T 24252-2019 as the testing standard, the compression rebound rate of silk cotton was tested. Each sample was tested three times, the average value was taken, and the test results were filled in Table 1.

[0054] (2) Washability The water washability of the samples was tested according to GB / T 5713-2013. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.

[0055] (3) Anti-ultraviolet performance The anti-ultraviolet performance of the samples was tested according to GB / T 18830-2009. Each sample was tested three times, and the average value was taken. The test results were filled in Table 1.

[0056] Table 1 Test results of samples of Examples 1-13 and Comparative Examples 1-2 Data analysis Combined with Table 1, it can be seen that the compression rates of Examples 1-3 are all 63% or more, and the elastic recovery rates are all 97% or more, indicating that the silk fabrics prepared in the present application have good wrinkle resistance, and the hydrophobic angles of Examples 1-3 are all 140° or more, indicating that the silk fabrics prepared in the present application have good water wash resistance; the 10-400nm ultraviolet blocking rates of Examples 1-3 are all 97% or more, indicating that the silk fabrics prepared in the present application have good ultraviolet resistance.

[0057] In Example 4 and Example 5, when preparing the polyetheramine composite anti-wrinkle agent, the mass ratios of polyetheramine complex A, polyetheramine complex B and emulsifier are not within the range specified in the present application. When the content of the emulsifier is too little, the particle size of the silicone composite system is difficult to be further improved, and the particle size uniformity is poor. Therefore, the polyetheramine anti-wrinkle agent is stratified, the stability is reduced, and the bonding performance with the silk fiber is difficult to be improved. When the content of the emulsifier is too much, the surface energy of the system is reduced too much, the dispersion performance is difficult to be further improved, and the overall stability of the system is also affected.

[0058] The emulsifier in Example 6 is only a single-component emulsifier, and a single-component emulsifier is difficult to further improve. The stability of the prepared polyetheramine composite anti-wrinkle agent is difficult to further improve, and the effect of improving the binding ability with silk fibers is poor. Therefore, the various performances of Example 6 are reduced.

[0059] In Example 7 and Example 8, when preparing the anti-ultraviolet agent, the mass ratios of the boron nitride complex, 1,4-butanediol and isophorone diisocyanate used are not within the range specified in the present application. When the content of the boron nitride complex is too little, the anti-ultraviolet effective ingredients decrease, and it is difficult to further improve the ultraviolet absorption effect. In addition, the content of active groups decreases, and the binding performance with silk fibers further decreases, so the overall performance is reduced.

[0060] In Example 9, when preparing the anti-ultraviolet agent, the finishing agent is replaced by toluene diisocyanate. Toluene diisocyanate has a large vapor pressure and poor stability.

[0061] In Example 10 and Example 11, when preparing the anti-ultraviolet agent, the temperature of the heating reaction is not within the range specified in the present application. When the reaction temperature is too low, the cross-linking effect between the components is reduced, and the stability of the prepared anti-ultraviolet agent is difficult to be further improved, so the overall performance is reduced; when the reaction temperature is too high, it will also affect the stability of the components in the system.

[0062] In Example 12, the boron nitride composite is replaced by boron nitride, which has too few active groups on the surface, and the dispersibility and compatibility in the system are difficult to improve. Therefore, the binding effect with the silk fiber is weakened, thus affecting the overall performance of the system.

[0063] In Example 13, when preparing the anti-UV agent, only the boron nitride complex and isophorone diisocyanate were compounded, the particle size uniformity of the entire system was difficult to be further improved, the overall stability of the system was reduced, and the binding performance between the anti-UV agent and the silk fiber was weakened, so the performance of Example 13 was reduced.

[0064] In Comparative Example 1, an anti-wrinkle agent is prepared by compounding tetraethyl orthosilicate with an emulsifier. Without adding a polyetheramine complex, it is difficult to fix the siloxane segments, thereby reducing the stability of the anti-wrinkle agent, and it is difficult to further improve the anti-wrinkle property and water washability.

[0065] The anti-UV agent in Comparative Example 2 is only an organosilicon composite system. The activity of the anti-UV agent added with isophorone diisocyanate is reduced, and its compatibility in the system is difficult to be further improved. At the same time, it is difficult to further protect the organosilicon composite system, and the bonding performance with the silk fiber is also reduced, which reduces the stability of the anti-UV agent. Therefore, the performance of Comparative Example 2 is reduced.

[0066] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A process for preparing durable pressing silk-cotton yarn-dyed fabric, characterized in that: The steps include: The silk fibers are soaked in an anti-wrinkle agent, and allowed to stand to allow the anti-wrinkle agent to fully contact the silk fibers, and then the silk fibers are taken out and dried to obtain treated silk fibers, and the treated silk fibers are spun to obtain silk fabrics, and the silk fabrics are dyed and dried to obtain silk cotton yarn-dyed fabrics; The anti-wrinkle agent comprises 180-200 parts of waterborne polyurethane emulsion, 21-31 parts of polyetheramine composite anti-wrinkle agent, 14-20 parts of anti-ultraviolet agent, 3-5 parts of dispersant and 2-4 parts of leveling agent. The polyetheramine composite anti-wrinkle agent comprises polyetheramine compound A, polyetheramine compound B and emulsifier.

2. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 1, characterized in that: The polyetheramine composite anti-wrinkle agent is prepared by the following method: The tetraethyl orthosilicate, polyetheramine ED-600 and acetic acid solution are mixed and dissolved in isopropanol to obtain polyetheramine complex A; polyetheramine T-403 and tetraethyl orthosilicate are mixed to obtain polyetheramine complex B; polyetheramine complex A and polyetheramine complex B are mixed and reacted to obtain an organosilicon composite system; an emulsifier is added to the organosilicon composite system and stirred to obtain a polyetheramine composite anti-wrinkle agent.

3. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 2, characterized in that: The mass ratio of the polyetheramine complex A, the polyetheramine complex B and the emulsifier is 0.58:1:(0.17-0.21).

4. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 2, characterized in that: The emulsifier includes dodecyl dimethyl benzyl ammonium chloride, hexadecyl trimethyl ammonium chloride, isomeric alcohol ether 1306 and isomeric alcohol ether 1308.

5. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 1, characterized in that: The anti-ultraviolet agent comprises a nitrogen-boron compound, 1,4-butanediol and a finishing agent.

6. A process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 5, characterized in that: The anti-ultraviolet agent is prepared by the following method: Ethyl acetate, hexamethylene diisocyanate, a finishing agent, water and gum arabic are mixed, and stirred until the system is completely dissolved to obtain a mixture. 1,4-butanediol is added to the mixture, and the mixture is heated and stirred to react to obtain a suspension. A nitrogen-boron complex is added to the suspension, and an anti-ultraviolet agent is obtained by ultrasonication.

7. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 6, characterized in that: The finishing agent is isophorone diisocyanate.

8. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 6, characterized in that: The mass ratio of the nitrogen-boron complex, 1,4-butanediol and isophorone diisocyanate is (3.1-3.5):1:5.

04.

9. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 6, characterized in that: The stirring temperature of the temperature-raising reaction is 45-55°C.

10. The process for preparing a durable pressing silk-cotton yarn-dyed fabric according to claim 6, characterized in that: The nitrogen-boron composite is prepared by the following method: Mix citric acid, ethylenediamine, boric acid and water, stir and react to obtain a nitrogen-boron complex.